Characterization and biofilm forming ability of diarrhoeagenic enteroaggregative Escherichia coli isolates recovered from human infants and young animals. (February 2015) - Vijay, Deepthi; Dhaka, Pankaj; Vergis, Jess; Negi, Mamta; Mohan, Vysakh; Kumar, Manesh; Doijad, Swapnil; Poharkar, Krupali; Kumar, Ashok; Malik, Satyaveer Singh; Barbuddhe, Sukhadeo Baliram; Rawool, Deepak B.
Graphical abstract: Abstract: Enteroaggregative Escherichia coli (EAEC) is an important pathotype that causes infection in humans and animals. EAEC isolates ( n  = 86) recovered from diarrhoeal cases in human infants (37) and young animals (49) were characterized as 'typical' and/or 'atypical' EAEC strains employing PCR for virulence associated genes ( cvd 432, aai A, ast A, pil S, irp 2, ecp, pic, aggR, aaf A, agg A, and agg 3A). Besides, biofilm formation ability of human and animal EAEC isolates was assessed using microtiter plate assay. In addition, the transcriptional profile of biofilm associated genes ( fis and ecp ) was also evaluated and correlated with biofilm formation assay for few selected EAEC isolates of human and animal origins. Overall, a diverse virulence gene profile was observed for the EAEC isolates of human and animal origins as none of the EAEC isolates revealed the presence of all the genes that were targeted. Nine 'typical' EAEC isolates were identified (6 from humans and 3 from animals) while, the majority of the isolates were 'atypical' EAEC strains. Isolation and identification of three 'typical' EAEC isolates from animals (canines) appears to be the first report globally. Further, based on the observations of the biofilm formation assay, the study suggested that human EAEC isolates in particular were comparatively more biofilm producers than that of the animal EAEC isolates. The fis gene was highly expressed in majority of 'typical' EAEC isolates and the ecp gene in 'atypical' EAEC isolates.